Fatigue of Binary Blend Composite Materials - Kader, Ekhlas Edan (Al-Nahrain Journal for Engineering Sciences, 2018)
Due to their very good mechanical properties of composite materials which led to a huge increase in its application in a lot of fields.Epoxy/ PS(polysulfide) composite materials  behavior in fatigue was reported. different weight fraction of PS (2%,4% and6%) were studied .Surface roughness properties of the blended composites were found for all weight fraction of PS and their fatigue properties are studied .Fatigue test was carried with rotating bending method. The loading in the test  was sinusoidal  wave type. The loading wave ratio is R = -1 and the frequency of loading is applied to avoid temperature rise with a frequency equal to 5Hz. Fatigue strength ,fatigue life and fatigue limit of the tested composites from standard curves are calculated. The addition of PS resulted in  an enhancement in  the fatigue values and cause the surface roughness to decrease at a considerable rate, the blend hardness is reduced considering shore A test.